Performance of the Social Service for Women's Empowerment and Child Protection in Distributing Social Assistance to Communities Affected by Covid-19 in Medan City - Sri Sudiarti; Trinaningsih Rambe (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to assess the performance of the P3A Social Service of Medan City in distributing social assistance to villages affected by COVID-19. This study uses a qualitative descriptive methodology with an inductive approach. Data triangulation approaches such as observation, documentation, and interviews were used to obtain data. Data reduction is the first step in the data analysis process, followed by data presentation and conclusion drawing. Using Agus Dwiyanto's theory with indicators of Productivity, Service Quality, Responsiveness, Responsibility, and Accountability, the research findings show that the performance of the Social Service in providing social assistance to people affected by COVID-19 is considered good. Based on the findings, the percentage of social assistance distributed has reached 90 percent. Suggestions that the author can give in order to improve the quality of services include: first, continue to socialize social assistance in the community, second, provide service posts and information about social assistance, and realize an increase in the number of Social Service personnel with knowledge of social assistance.